A new URANS based approach on the prediction of vertical motions of a surface combatant in head waves. (15th August 2018) - Cakici, Ferdi; Kahramanoglu, Emre; Duman, Suleyman; Alkan, Ahmet Dursun
Abstract: In this study, wave excitation and radiation terms in 2DOF equations of vertical ship motion are obtained by using a URANS solver based on the finite volume method. The DTMB 5512 hull form is chosen for the calculations at the Froude number of 0.41. Numerical simulations are performed for 7 different regular wave conditions. First, in the regular wave, the excitation heave force and pitch moment with the related phase angle are computed while the ship is fixed to heave and pitch motions. Then, the body is forced to oscillate in the heave and pitch directions with a certain frequency and the radiation coefficients are obtained. After finding the excitation and radiated terms, the 2DOF vertical ship motion equations are solved in the frequency domain, and motion transfer functions are plotted. The results are compared with those obtained through strip theory, fully nonlinear URANS approach and experiments. The new URANS based approach presented in this paper offers a more accurate prediction of vertical ship motions compared to strip theory outputs because it takes the viscous effects and free surface nonlinearities into account. The new URANS based approach can be considered as a better alternative to the fully nonlinear URANS approach. Highlights: The prediction of ship vertical motions at high speed case by using a new method. Radiation and excitation terms are calculated separately by URANS approach. The present method is a good alternative for prediction the vertical ship motions. The URANS results are validated against the experimental data.